1986
DOI: 10.1111/j.1365-246x.1986.tb03835.x
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake deformations in the Lisan deposits and seismotectonic implications

Abstract: Earthquake deformations and induced sedimentary structures preserved in Quaternary sediments include faults, folds, fissures, slumps, sand boils and other effects of liquefaction. Such deformations and structures are well preserved in the Lisan deposits of the Dead Sea. Of most importance are the fold-type deformations known as dbcollement structures which are present all along the eastern side of the Lisan and seem to decrease gradually westwards to disappear in the middle of the Lisan. These may indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…El-Isa and Mustafa, 1986;Maltman, 1994b;Neuweiler et al, 1999;Onasch and Kahle, 2002;Hildebrandt and Egenhoff, 2007;Moretti and Sabato, 2007; been suggested (Kennett and Fackler-Adams, 2000), but this can also be ruled out for the same reason.…”
Section: Non-seismic Originsmentioning
confidence: 92%
“…El-Isa and Mustafa, 1986;Maltman, 1994b;Neuweiler et al, 1999;Onasch and Kahle, 2002;Hildebrandt and Egenhoff, 2007;Moretti and Sabato, 2007; been suggested (Kennett and Fackler-Adams, 2000), but this can also be ruled out for the same reason.…”
Section: Non-seismic Originsmentioning
confidence: 92%
“…Huge hyperpycnal flows, with high kinetic energy, may follow complex paths on lake bottoms with successive reflections from lake basin margins, as described in a fjord by Pickering and Hiscott (1985). Since the correlation established by Sims (1973Sims ( , 1975 between disturbed layers and surveyed recent earthquakes in an artificial lake, various lacustrine accumulations (in situ or outcropping) have been used to assess late Quaternary seismicity in active tectonic settings (Hempton and Dewey, 1983;Doig, 1985;El-Isa and Mustafa, 1986;Shiki et al, 2000). Several investigations on continental sediments have underlined causal relations between a Late Pleistocene increase of recorded seismicity and the rapid post-LGM deglaciation (Mörner, 1996;Beck et al, 1996).…”
Section: Lacustrine Realmsmentioning
confidence: 99%
“…Liquefaction and fluidization can be induced by many natural processes, including overloading, unequal loading, wave-induced cyclical and/or impulsive stresses, sudden changes in groundwater level, and earthquakes (Owen, 1987(Owen, , 1996. Soft-sediment deformation structures related to seismically-induced liquefaction or fluidization (seismites, sensu Seilacher, 1969sensu Seilacher, , 1984sensu Seilacher, , 1991 have been analysed by many authors and reported from all sedimentary environments, but they seem to be particularly common in lacustrine successions (Sims, 1973(Sims, , 1975(Sims, , 1976Ben-Menahem, 1976;Hesse and Reading, 1978;Sedimentary Geology 196 (2007) 31 -45 www.elsevier.com/locate/sedgeo Hempton and Dewey, 1983;Seilacher, 1984;Plint, 1985;El-Isa and Mustafa, 1986;Anand and Jain, 1987;Davenport and Ringrose, 1987;Scott and Price, 1988;Ringrose, 1989;Beck et al, 1992;Karlin and Abella, 1992;Van Loon et al, 1995;Beck et al, 1996;Alfaro et al, 1997;Lignier et al, 1998;Malkawi and Alawneh, 2000;RodrĂ­guez Pascua et al, 2000;Becker et al, 2002;Leroy et al, 2002;Bowman et al, 2004;Migowski et al, 2004;Weidlich and Bernecker, 2004;Schnellmann et al, 2005). Moreover, some homogeneous silty beds in lacustrine environments have been interpreted as seismites (Doig, 1986(Doig, , 1990Shilts and...…”
Section: Introductionmentioning
confidence: 96%